Changes in Heart Rate Variability in a Premature Infant with Hydrocephalus - Uhrikova, Zuzana; Kolarovszki, Branislav; Javorka, Kamil; Javorka, Michal; Matasova, Katarina; Kolarovszka, Hana; Zibolen, Mirko (American Journal of Perinatology Reports, 2012)
Objective To define changes of heart rate variability in premature infant with hydrocephalus before and after drainage procedure.Study Design The authors report a case of a premature infant with hydrocephalus with analysis of heart rate variability before and after drainage procedure. Three subsequent recordings of the electrocardiography and heart rate variability were done: the first at the age of 22 days before insertion of ventriculoperitoneal shunt, the second at the age of 36 days with functional shunt, the third at the age of 71 days (before discharge).Results Before drainage operation, there was reduced heart rate variability in time and spectral domains, and sympathetic activity was dominant. After surgery, an increase in heart rate variability parameters was found, particularly with spectral analysis. The ratio of low-frequency/high-frequency band and relative power of the low-frequency band decreased, reflecting enhanced parasympathetic activity.Conclusion Results of the heart rate variability analysis in a preterm infant with hydrocephalus before and after drainage procedure showed marked improvement in chronotropic cardiac regulation. Evaluation of heart rate variability in premature infants with hydrocephalus with increased intracranial pressure can be an additional method for monitoring of cardiac dysregulation and improvement of the cardiovascular control after successful drainage procedure.
Keywords: heart rate variability; newborn; hydrocephalus